"Because I'm still the parent, that's why!" Parental legitimate authority during emerging adulthood. (May 2014) - Padilla-Walker, Laura M.; Nelson, Larry J.; Knapp, Darin J.
The current study sought to examine the discrepancies between parent and child reports of legitimate parental authority, to identify heterogeneity in college students' perceptions of parental legitimate authority, and to examine potential variables that might differ as a function of group membership. Participants ( M age = 19.65, SD = 2.00, range = 18–29) consisted of 438 undergraduate students (320 women, 118 men) and at least one parent (376 mothers, 303 fathers). Results suggested that parents reported higher levels of legitimate authority than did children. Results found three groups and group membership varied as a function of perceptions of adult status, parental financial support, parental control, and the quality of the parent–child relationship. Discussion focuses on the implications of these findings for the parent–child relationship.